A practical guide to test blueprinting. (3rd August 2019) - Raymond, Mark R.; Grande, Joseph P.
Abstract: A test blueprint describes the key elements of a test, including the content to be covered, the amount of emphasis allocated to each content area, and other important features. This article offers practical guidelines for developing test blueprints. We first discuss the role of learning outcomes and behavioral objectives in test blueprinting, and then describe a four-stage process for creating test blueprints. The steps include identifying the major knowledge and skill domains (i.e. competencies); delineating the specific assessment objectives; determining the method of assessment to address those objectives; and establishing the amount of emphasis to allocate to each knowledge or skill domain. The article refers to and provides examples of numerous test blueprints for a wide variety of knowledge and skill domains. We conclude by discussing the role of test blueprinting in test score validation, and by summarizing some of the other ways that test blueprints support instruction and assessment.